A report on neurogenic bladder in COVID-19 vaccine-associated acute transverse myelitis - Zainudin, Muhamad Faizal; Hasim, Mohd Razali; Martin, Christina Eleanor; Chandrabose, Thanalactchumy (Springer Nature, 2024)
Introduction: Acute transverse myelitis (ATM) is a rare neurological complication of Coronavirus disease (COVID-19) vaccines. Various vaccines have been linked to ATM, such as non-replicating viral vectors, ribonucleic acid, and inactivated vaccines. An ATM case is presented here involving the BNT162b2 vaccine leading to asymmetrical incomplete paraplegia and neurogenic bladder. Case presentation: A 66-year-old male developed urinary retention one day after his second dose of the BNT162b2 vaccine, followed by rapidly progressing lower limb weakness. Clinical examination showed asymmetrical paraparesis, reduced sensation below the T8 level, including perianal sensation, and loss of ankle and anal reflexes. Laboratory tests were largely unremarkable, while the spine MRI revealed thickened conus medullaris with a mild increase in T2/STIR signal intensity and subtle enhancement post gadolinium. Following treatment with methylprednisolone, plasmapheresis, and immunoglobulin, and a rehabilitation program, the patient achieved good motor and sensory recovery, but the bladder dysfunction persisted. Single-channel cystometry indicated neurogenic detrusor underactivity and reduced bladder sensation, as evidenced by low-pressure and compliant bladder. The urethral sphincter appeared intact or overactive. The post-void residual urine was significant, necessitating prolonged intermittent catheterisation. Discussion: Bladder dysfunction due to the COVID-19 vaccine-associated ATM is not as commonly reported as motor or sensory deficits. To our knowledge, this is the first case to highlight a neurogenic bladder that necessitates prolonged intermittent catheterisation as a consequence of COVID-19 vaccine-associated ATM. This report highlights the rare complication of the neurogenic bladder resulting from the BNT162b2 vaccine. Early detection and treatment are crucial to prevent long-term complications.